Czy refleksyjność chroni nas przed depresją? - Dolińska-Zygmunt, Grażyna; Grzybek, Radosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article contains the author's research concerning differences in the level of reflectiveness between healthy persons and the ones with diagnosed depression. The choice of variables was determined by an attempt at verifying empirical reports indicating that depressive persons in comparison with non-depressive ones perceive reality more realistically, i.e. are resistant to certain specific positive illusions, probably connected with higher reflectiveness. The results confirm the hypothesis regarding a higher degree of refleciveness in depressive persons. However, higher reflectiveness and the resistance to positive illusions connected with it do not influence the mood and mental well-being favourably. What is more, it does not protect depressive persons against negative illusions and cognitive mistakes described at length by cognitive psychology. The results obtained lay a new outlook on psychotherapy of depression. Concentrating on a directed activity (even a short-term one) and reducing reflectiveness may result in the appearance of positive illusions indispensable for correct and effective functioning and eventually in the reduction of depressive symptoms. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 220-229